Die Gemeinsame Agrarpolitik der EU: Flaggschiff-Politik oder ewige Reformruine? - Sebastian Lakner; Norbert Röder (Wirtschaftsdienst, 2024)
– The article describes the reform path of the EU's Common Agricultural Policy (CAP) since 1992. The largest share of agricultural subsidies in Germany ( exteuro7.2 billion) is granted through the CAP with significant room for manoeuvre in terms of content. Between 1992-2013, the old, protectionist CAP was to a large extent successfully transformed into a liberalised CAP. Since 2014, the CAP reform debate has increasingly focussed on the provision of public goods. The CAP is currently characterised by the idea of simultaneously achieving income and environmental targets. In the CAP's current form, this is associated with considerable inconsistencies and weaknesses.
Keywords: Q15; Q18; Q57; 330; Agrarpolitik; EU-Staaten; Agrarpolitik; EU-Staaten